2011
DOI: 10.1001/archophthalmol.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Response to Amblyopia Treatment in Children

Abstract: To determine whether age at initiation of treatment for amblyopia influences the response among children 3 to less than 13 years of age with unilateral amblyopia who have 20/40 to 20/400 amblyopic eye visual acuity.Methods: A meta-analysis of individual subject data from 4 recently completed randomized amblyopia treatment trials was performed to evaluate the relationship between age and improvement in logMAR amblyopic eye visual acuity. Analyses were adjusted for baseline amblyopic eye visual acuity, spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
184
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 290 publications
(194 citation statements)
references
References 31 publications
8
184
0
2
Order By: Relevance
“…A large number of studies agree that there is residual plasticity in amblyopes beyond the once assumed age of 6 or 8 years and even into adulthood (Chen, Song, & Wu, 2003), emphasizing either the importance of age (Fulton & Mayer, 1988;Holmes et al, 2011;Rutstein & Fuhr, 1992;Sattler, 1927) or of compliance (Arnold, Armitage, & Limstrom, 2008;Mintz-Hittner & Fernandez, 2000;Park, Hwang, & Ahn, 2004), or the interdependence of the two (Oliver et al, 1986) for successful treatment. In accordance with the MOTAS/ROTAS studies (Stewart et al, 2004b(Stewart et al, , 2007a(Stewart et al, , 2007b and a meta-analysis of the Amblyopia Treatment Studies (ATS, Holmes et al, 2011), we found decreasing susceptibility of the visual system with age to the enforced use of the amblyopic eye.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…A large number of studies agree that there is residual plasticity in amblyopes beyond the once assumed age of 6 or 8 years and even into adulthood (Chen, Song, & Wu, 2003), emphasizing either the importance of age (Fulton & Mayer, 1988;Holmes et al, 2011;Rutstein & Fuhr, 1992;Sattler, 1927) or of compliance (Arnold, Armitage, & Limstrom, 2008;Mintz-Hittner & Fernandez, 2000;Park, Hwang, & Ahn, 2004), or the interdependence of the two (Oliver et al, 1986) for successful treatment. In accordance with the MOTAS/ROTAS studies (Stewart et al, 2004b(Stewart et al, , 2007a(Stewart et al, , 2007b and a meta-analysis of the Amblyopia Treatment Studies (ATS, Holmes et al, 2011), we found decreasing susceptibility of the visual system with age to the enforced use of the amblyopic eye.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…Earlier detection of visual or hearing deficits improve outcome. [1][2][3][4] Vision and hearing screening programmes are based on the same general principles, but vary both within and across European Union (EU) countries, regarding tests used, age of testing, frequency of testing, professions involved in screening, referral procedure, funding, and coverage. Such differences can result in health inequities.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal age for treatment is not clear, but a correction before the age of 7 or even 3 years, depending on the study, seems advisable. 9,10 Moreover, while a patient could potentially simulate visual function loss with explicit behavioral tests in cases of hysteria or malingering, 11 he/she would be unable to do so with an implicit electrophysiologic index as measured with sVEP. Second, unlike standard event-related potential (ERP) measures 12 such as the flash potential, the electrophysiologic response of interest confines to a predetermined frequency known by the experimenter, increasing objectivity, 4 and requiring minimal analysis procedures.…”
mentioning
confidence: 99%